PENGGUNAAN METODE DEMONSTRASI DALAM PEMBELAJARAN IPA TENTANG PERKEMBANGBIAKAN VEGETATIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Muqoddas, Ifsantin; Widyasari, Widyasari; Istianah, Istianah (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2015)
Classroom action research is initiated by studentsâ result on the Sciences, especially in vegetative propagation subject. This classroom action research aims to improve learning outcomes for Sciences in developing vegetative objects by using demonstrations in grade six of National Elementary School two of Ciasmara on the academic year 2014â2015. Classroom Action research was conducted in two cycles. Based on data analysis of student learning outcomes, the result of the first cycle is quite successful to improve learning achievement. The early findings indicated an increase of the average value of the initial test class reached 55 and then increased to 64 at the first cycle, but the value is still classified under the category of sufficient. The results of the data analysis of student learning outcomes in the second cycle showed excellent improvement was shown from the comparison of the first cycle of the average is 64 and increased in the second cycle become 71. It can be concluded that the learning outcomes in the second cycle already suited with the standard of minimum criteria. Therefore, it can be realized that the method of demonstration, student learning outcomes of The Sciences in Elementary School on vegetative propagation subject had been increased.